Geochemical Modeling of Water-Rock Interaction in UppermostRegional Aquifer in Arar Area - Al-Suhail, Qusay; Al-Mansoury, Hussein; A-Mallah, Enas (Iraqi Journal of Science, 2025)
Geochemical modeling technique was used to study the chemical evolution ofthe Upper most regional aquifer in Wadi Arar area. This aquifer composed fromlimestone, dolomite and some scattered or interbedded anhydrite and gypsum.Karstic terrains are highly developed in the area. Geochemical calculations showedthat the studied groundwater are supersaturated and undersaturated with carbonateand sulfate minerals respectively. Four flow paths were selected to determine themain chemical reactions thought to be responsible for the variation of chemicalcomposition of the system under consideration and also to evaluate the amount ofmass transfer of selected mineral phases. Many reaction path models have beenidentified, mainly calcite precipitation, de-dolomitization and cation exchange ofCa for Na for paths 11 and 12 (eastern parts) and calcite precipitation,dolomitization and cation exchange of the Na for Ca for the western parts, flowpaths 2 and 5.